Understanding the linkages between racial/ethnic discipline gaps and racial/ethnic achievement gaps in the United States - Gopalan, Maithreyi (Education Policy Analysis Archives, 2019)
This study estimates racial/ethnic discipline gaps, using multiple measures of school discipline outcomes, in nearly all school districts in the United States with data collected by the Office of Civil Rights between 2013 and 2014. Just like racial/ethnic achievement gaps, discipline gaps also vary substantially, ranging from negative to greater than two standard deviations, across districts. However, unlike the correlates of racial achievement gaps, the extensive set of district-level characteristics available in the Stanford Education Data Archive (SEDA) including economic, demographic, segregation, and school characteristics, explain roughly just one-fifth of the geographic variation in Black-white discipline gaps and one-third of the variation in Hispanic-white discipline gaps. This study also finds a modest, statistically significant, positive association between discipline gaps and achievement gaps, even after extensive covariate adjustment. The results of this analysis provide an important step forward in determining the relationship between two forms of persistent inequality that have long plagued the U.S. education system.